2009
DOI: 10.1111/j.1447-0349.2009.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating complexities: An ethnographic study of intellectual disability and mental health nursing in New Zealand

Abstract: This paper presents the findings from a study undertaken to describe nursing practice in one dual diagnosis (DD; coexisting mental illness and intellectual disability) inpatient unit in New Zealand. A focused ethnographic approach (using fieldwork observations, a review of documents, and five semistructured interviews) was used to gather data. A model of culture was used to analyze data to allow a description of DD nursing practice. Additionally, this framework allowed for an exploration of the artefacts, valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 31 publications
(40 reference statements)
0
43
0
Order By: Relevance
“…The origin of the primary research papers could be identified as: UK (Barriball and Clark, 2005;Clark, 2007;Jenkins, 2009;Donner et al, 2010;Bollard et al, 2012;Read and Rushton, 2013;Rose et al, 2012aRose et al, , 2012b, US (Hahn, 2003), Netherlands (Klooster et al, 2009) New Zealand (Taua and Farrow, 2009;Taua et al, 2012) and Israel (Werner and Stawski, 2012). Of the 13 articles included, three distinct categories were apparent which will be discussed:…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The origin of the primary research papers could be identified as: UK (Barriball and Clark, 2005;Clark, 2007;Jenkins, 2009;Donner et al, 2010;Bollard et al, 2012;Read and Rushton, 2013;Rose et al, 2012aRose et al, , 2012b, US (Hahn, 2003), Netherlands (Klooster et al, 2009) New Zealand (Taua and Farrow, 2009;Taua et al, 2012) and Israel (Werner and Stawski, 2012). Of the 13 articles included, three distinct categories were apparent which will be discussed:…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Without clear guidance and frameworks for practice, nurse's confusion will remain problematic. In addition a lack of appropriate assessment tools leaves nurses lacking in confidence when they are faced with a person with learning disability and mental illness (Taua and Farrow, 2009;Taua et al, 2012;Donner et al, 2010). A lack of knowledge may promote the continued problem of diagnostic overshadowing with the complex needs of these individuals not being identified (Taua et al, 2012;Donner et al, 2010).…”
Section: Implications For Practicementioning
confidence: 93%
See 1 more Smart Citation
“…However, the multiple challenges that nurses face in responding to the mental health needs of this group is critical to understanding the development of best care (Doyle 2000). Effective, evidenced‐based DD nursing practice is dispersed, inadequately defined, and has a poor research infrastructure, yet it is required to respond to all of the contemporary policy and practice requirements related to both ID and mental health nursing (Doyle 2000; Taua & Farrow 2009). What is evident is that there is a clear absence of the articulation of the roles and responsibilities of the nurse.…”
Section: Focus Of This Reviewmentioning
confidence: 99%
“…Individuals with intellectual disabilities (ID) and dual diagnosis of ID and psychopathology (i.e. behavioural, emotional or psychiatric disturbances) have a wide range of cognitive, physical, psychiatric, communication and social needs (Taua & Farrow ), requiring various services (Schieve et al . ).…”
Section: Introductionmentioning
confidence: 99%